Federated or Non-Federated Sports: The Influence on Children, the Youth Population and Family Life - José Santiago Álvarez Muñoz; Mª Ángeles Hernández Prados; César Palazón Segura (MDPI AG, 2024)
Family time must be combined with the personal time of each of its members, with special importance regarding children due to the need for attention and monitoring by parents of their performance. Within the leisure of minors in the home, physical activity and sports are the most in-demand typologies, thus some of them participate in federated clubs, attending a more institutionalized or professional sport, while others develop in an environment based on entertainment. In this way, depending on the demand for these activities, it leads to a series of different consequences in the family environment. The main objective of this study is to establish whether or not children's attendance at federated sports affects family dynamics. A total of 224 Spanish families with children from 6 to 18 years of age who practice sport activities participated and completed a questionnaire with 36 items about the family's involvement in children's sports. The results show that parents with children participating in federated sports have a more positive perception of their children's sports practices; they provide greater support to their children regarding their performance and see this activity as an excellent opportunity for education in values. However, they do identify it as an obstacle to the development of family leisure practices, resulting in an element that conditions family reconciliation. In this way, there is a need to establish alliances between families and sports professionals, providing family participation bodies in sports clubs and providing a better conciliation time to accommodate family time.